Indoor Optical Wireless MIMO System With an Imaging Receiver - Dambul, K; O'Brien, D; Faulkner, G (2011)
This letter reports an experimental demonstration of an indoor optical wireless multiple-inputmultiple-output (MIMO) system with an imaging receiver. The system setup consists of a 2 × 2 array of white light-emitting diodes (LEDs) and a 3 × 3 photodetector array, separated by a range of 2 m. The system operates at a bit rate of 2 Mb/s/channel, with error-free operation at certain positions within the system coverage area. An overview of the design specifications, optical design, and experimental setup are reported in this letter, together with results and discussion of how the system might be improved. © 2006 IEEE.